2007
DOI: 10.1038/sj.ejcn.1602815
|View full text |Cite
|
Sign up to set email alerts
|

Relative validity of a food frequency questionnaire used in the Inter99 study

Abstract: Objective: To evaluate the validity of the Inter99 food frequency questionnaire (FFQ) compared with a 28-days' diet history and biomarkers. Subjects: A random sample of 13 016 individuals were drawn from a general population and invited for a health screening programme. Participation rate was 52.5%. All high-risk individuals were re-invited for assessment after 1 and 3 years and completed a 198-item FFQ at all three occasions. Participants attending for 3 years follow-up were invited to participate in the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 38 publications
11
68
1
Order By: Relevance
“…Many studies have reported an increase in correlation coefficients after adjusting for energy (Ahn et al, 2007;Brunner et al, 2001;Shim et al, 2002;Watson et al, 2009;Willett, 1998), but we found no increase in correlation coefficients after energy adjustment. Our finding was supported by other studies, which reported either a decrease or no improvement in correlation coefficients (Du et al, 2009;Fumagalli et al, 2008;Quandt et al, 2007;Toft et al, 2008). Quandt et al (2007) postulated that this result comes from respondents' underreporting of some macronutrients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Many studies have reported an increase in correlation coefficients after adjusting for energy (Ahn et al, 2007;Brunner et al, 2001;Shim et al, 2002;Watson et al, 2009;Willett, 1998), but we found no increase in correlation coefficients after energy adjustment. Our finding was supported by other studies, which reported either a decrease or no improvement in correlation coefficients (Du et al, 2009;Fumagalli et al, 2008;Quandt et al, 2007;Toft et al, 2008). Quandt et al (2007) postulated that this result comes from respondents' underreporting of some macronutrients.…”
Section: Discussionsupporting
confidence: 82%
“…However, the correlation coefficient for carrots was low; this may be because carrots are not usually consumed in isolation from other foods. The Spearman's correlation coefficient for calcium was similar or higher compared to other studies (Fregapane & Asensio-Garcia, 2000;HackerThompson et al, 2009;Jaceldo-Siegl et al, 2010;Lyu et al, 2007;Toft et al, 2008;Watson et al, 2009;Zemel et al, 2010). The correlation coefficient for sodium was low, but this result was also found in many other studies (Carithers et al, 2009;Fumagalli et al, 2008;Jaceldo-Siegl et al, 2010).…”
Section: Discussionmentioning
confidence: 34%
“…A family history of diabetes was defined as having a first-degree relative with diabetes. Dietary intake was assessed by a validated food-frequency questionnaire of dietary intake during the previous month [28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity outside the training was assessed using a question in The Danish Health and Morbidity Survey 2005 Questionnaire [8]. Food intake was assessed using a modified 7-day version of the Inter99 food frequency questionnaire [9] and the energy intake was determined with the aid of Master Diætist data software (Anova Data A/S, Holte, Denmark).…”
Section: Methodsmentioning
confidence: 99%